DESAKRALISASI WAYANG PURWA LAKON RUWAT - Mashuri, Mashuri (Balai Bahasa Jawa Timur, 2007)
In the culture of Java, the wayang purwa (shadow play with leather puppets often dramatizing theme from Hindu epics) is important, central and sacral. Finally, many Javanese identify themselves to the characters in the wayang. The main factor is because the wayang is considered as the oldest of culture product, and also it can glorify the grandeur and the sacrality. The wayang sacrality can be found in ruwat act. The act in old treasure is ini some serat and suluk, consides that the act is not only a common story. But, the sacrality value that is glorified in Javanese culture, either in the wayang show or ruwatan, almost can not be found the presentation in Durga Umayi text, worked by YB Mangunwijaya. The are so many texts that have the? tendency to dig up the sacrality of wayang. This propane process has occurred not only to the characters of wayang that are considered as sacral's and guide's eyes only, but also in the essence of the plot and the value of the story. The Durga Umayi text seems that is presented to be comparable with the wayang disourse that has been built and established. In the text consists of desacralization ruwat act with some strategies, like blurring of binary opposition, reversal, and some other deconstruction strategy.